2023
DOI: 10.3389/frcmn.2023.1179626
|View full text |Cite
|
Sign up to set email alerts
|

Network intelligence vs. jamming in underwater networks: how learning can cope with misbehavior

Abstract: In this paper, we present a machine-learning technique to counteract jamming attacks in underwater networks. Indeed, this is relevant in security applications where sensor devices are located in critical regions, for example, in the case of national border surveillance or for identifying any unauthorized intrusion. To this aim, a multi-hop routing protocol that relies on the exploitation of a Q-learning methodology is presented with a focus on increasing reliability in data communication and network lifetime. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The outcomes demonstrated that these routing algorithms significantly impacted network performance. A machinelearning method to defend against jamming assaults in underwater networks was presented by Mertens et al [17] This applies to security applications where sensor devices are placed in high-risk areas. The proposed approach is efficient in reducing unnecessary energy use, according to extensive simulation and performance research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outcomes demonstrated that these routing algorithms significantly impacted network performance. A machinelearning method to defend against jamming assaults in underwater networks was presented by Mertens et al [17] This applies to security applications where sensor devices are placed in high-risk areas. The proposed approach is efficient in reducing unnecessary energy use, according to extensive simulation and performance research.…”
Section: Literature Reviewmentioning
confidence: 99%